Magnetism and magnetic properties of Ti-rich titanomagnetite and its tendency for alteration in favour of titanomaghemite - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2010)
The study of the Ti-rich titanomagnetite (Ti-Mt) and the low-temperature oxidized Ti-Mt bearing basalts has been undertaken. High magnetic susceptibility of the Ti-rich Ti-Mt basalts does not correspond to high spontaneous magnetization. The decrease of spontaneous magnetization with increasing content of ulv¨ospinel is evidenced. The spontaneous magnetization in ferromagnetics and ferrimagnetics originate in the magnetic domains, but the domain structure in the Ti-rich larger Ti-Mt grain sizes is rarely developed. The cause of high magnetic susceptibility of the Ti-rich Ti-Mt stems probably from the molecular field of the two sub-lattice structure of the Ti-Mt. Alternative explanation: In the low magnetic fields, the permeability of the mixed ferrites increases with increasing temperature and reaches the extreme maximum at the temperature closely below the Curie temperature of material. Similar behaviour have been shown also by the Ti-rich Ti-Mt-es. Rapid decrease of the magnetic crystalographic anisotropy with temperature and the decrease in intensity of the exchange interactions are responsible for this effect. So, the increase of Ti4+ ions in the titanomagnetite results in the increase of magnetic susceptibility of the Ti-rich Ti-Mt-es. The problem of the extremely low magnetic susceptibility in the basalts with lowtemperature oxidized phase consists in the following: along with the low-temperature oxidation of Fe2+ to Fe3+ ion and the formation of vacancies in creating titanomaghemite, the rearrangement of magnetic moments in initial Ti-rich Ti-Mt has taken place. The initial state had a more anti-ferromagnetic arrangement with high content of ulv¨ospinel of high non-collinearity. High magnetism of the initial Ti-Mt was due to the action of the molecular field. During the above-mentioned process this original state was broken down, and the magnetic susceptibility was rapidly decreased. A completely new ferrimagnnetic arrangement of magnetic moments of the sub-lattices has been established in the titanomaghemite.